(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
A comparative analysis of the misuse of PAS between Italy and the United Kingdom: an exogenous factor within family law disputes ABSTRACT: This paper aims to elucidate the dynamics and strategies employed by abusive individuals who exploit gender stereotypes to manipulate the justice system in their favor. Increasingly, courts are unable to adequately protect victims of domestic violence due to the erroneous reliance on counteraccusations of parental alienation, which are artfully raised by former abusive partners. These allegations are unfounded in law and scientifically disproven, yet they are held in enormous esteem by the judiciary. Instead, the courts should be reminded of the careful balancing of opposing interests that arise in the context of family law proceedings. This should be done without disregarding the examination of the concrete case and the overriding interest of protecting the offspring. SOMMARIO: 1. PAS e DARVO: dinamiche e strategie tipiche dei procedimenti di diritto di famiglia - 2. Discriminazione di genere nelle controversie famigliari - 3. La censura della PAS da parte di Organizzazione Mondiale della Sanità e Nazioni Unite - 4. L’overruling della PAS nelle corti della Family Division dell’Alta Corte di Inghilterra e Galles - 5. Il rigetto della PAS nella recente giurisprudenza italiana - 6. Conclusioni.